Optimization of Surfactin Production by Bacillus amyloliquefaciens MD4-12 using Response Surface Methodology - AHMAD WIBISANA; WAHONO SUMARYONO; MIRAWATI SUDIRO; PRATIWI PUDJILESTARI SUDARMONO (Microbiology Indonesia, 2015)
Surfactin is a lipopeptide biosurfactant that show potential biomedical application due to its activities such as antiviral, antibacterial, antifungi, anticancer, and antimycoplasma. Bacillus amyloliquefaciens MD4-12, isolated from oil-contaminated soil, produced promising yield of surfactin in McKeen medium. The production of surfactin was influenced by many fermentation process parameters such as carbon, nitrogen, minerals and also environmental conditions such as pH and agitation. Therefore, to obtain high yield of surfactin by Bacillus amyloliquefaciens MD4-12, optimization of process production was conducted in shake flask fermentation using response surface methodology. McKeen medium composition was used as basal medium.Â  Screening of the best carbon and nitrogen source were selected in preliminary experiments followed by selection of the influencing significant parameters on surfactin production using Plackett-Burman design. Selected parameters were optimized by central composite design and for the data analysis was used response surface methodology. The result showed that the optimum medium composition contained (g/L) 45.0 glucose, 6.33 urea, 1.0 monosodium glutamate, 1.85 MgSO4.7H2O, 0.4 KCl, 0.5 K2HPO4 and 0.5 mL trace elements. The surfactin yield at optimal condition was 1.25 g/L, increased 2.4 times compared to condition prior to optimization.Â